2021
DOI: 10.3390/nu13082657
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Salmonella Activity and Peptidomic Profiling of Peptide Fractions Produced from Sturgeon Fish Skin Collagen (Huso huso) Using Commercial Enzymes

Abstract: This study investigated peptide fractions from fish skin collagen for antibacterial activity against Escherichia coli and Salmonella strains. The collagen was hydrolyzed with six commercial proteases, including trypsin, Alcalase, Neutrase, Flavourzyme, pepsin and papain. Hydrolyzed samples obtained with trypsin and Alcalase had the largest number of small peptides (molecular weight < 10 kDa), while the hydrolysate produced with papain showed the lowest degree of hydrolysis and highest number of large peptid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 50 publications
(70 reference statements)
0
10
0
Order By: Relevance
“…Additionally, it is often accompanied by a high cost of production, leading to a longer purification process [ 14 , 70 ]. Recent research on antimicrobial marine peptides, or their fractions thereof, are reported to have a molecular weight <10 kDa and a high degree of antimicrobial activity [ 71 ]. Some of the techniques employed for the preparation and purification of MBAPs are listed in Table 1 .…”
Section: Marine Bioactive Peptides (Mbaps)mentioning
confidence: 99%
“…Additionally, it is often accompanied by a high cost of production, leading to a longer purification process [ 14 , 70 ]. Recent research on antimicrobial marine peptides, or their fractions thereof, are reported to have a molecular weight <10 kDa and a high degree of antimicrobial activity [ 71 ]. Some of the techniques employed for the preparation and purification of MBAPs are listed in Table 1 .…”
Section: Marine Bioactive Peptides (Mbaps)mentioning
confidence: 99%
“…Fish protein hydrolysate (FPH) is a proteinderived substance that has been hydrolyzed to produce amino acid and peptide components of varying molecular sizes. It is widely known to have bioactive peptide with functional properties such as antioxidants (Sohaib et al, 2017;Nurilmala et al, 2020;Shiao et al, 2021), antibacterial (Trang and Pasuwan, 2018;Atef et al, 2021), anti-Inflammatory (Da Rocha et al, 2018), and antihypertensive (Abachi et al, 2019;Naik et al, 2021). Several proteases have been reported to be used for the production of FPH such as orientase, protease XXIII, trypsin, bromelain, papain, protamex, bovine pancreatin 6.0, neutrase 1.5MG, and alcalase (Ren et al, 2007;Hsu, 2010;Šližytė et al, 2016;Yathisha et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The cryptides in collagen hydrolysate have been shown to have angiogenic, mitogenic (Banerjee & Shanthi, 2016), and antibacterial properties ( Ennaas et al, 2016;Atef et al, 2021). The administration of collagen peptides significantly improved exercise-athletic injury pain (Dressler et al, 2018;Zdzieblik et al, 2021) and accelerated healing in patients with Achilles tendonitis (Praet et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Baehaki et al, (2016) reported that fish skin cryptides produced with bacterial collagenase inhibited angiotensin I-converting enzymes and were anti-cancer. On the other hand, cryptides derived from collagen showed antimicrobial activity against Salmonella spp., Escherichia coli, and Staphylococcus aureus (Atef et al, 2021). However, the antimicrobial potential of collagenderived cryptides still needs to be extensively researched despite the protein diversity from different organisms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation